Poetics of Love in Henry James’s “The Beast in the Jungle” - Mohamad Mosavat; Tahereh Rezaei (Journal of Language and Literature, 2022)
May and Marcher in Henry James’s “The Beast in the Jungle” pursues an odd relationship interpreted by James’s critics as fraudulent, self-victimizing, or queer. While May is reduced to a witness to Marcher’s psychosomatic complexities, an evidence reliable to justify Marcher’s troubled heterosexuality, Marcher is deprived of any romantic yearnings for her. This article, departing from simplistic psychosexual interpretations having ended up demoting May to an inferior position and Marcher to a homosexual character, suggests the main problem of their relationship is the contrast between their love styles. In this relationship, the communication is prevented not so much by May’s subordinate silence/assent as by Marcher’s narcissism. John Allan Lee’s typology of love helps individually explicate each character’s psychological traits and romantic advances under Lee’s comparing terms of eros/ludus and storge/mania. The result of this case-by-case analysis is to prove their relationship is nothing but the obsession Dorothy Tennov redefines in her limerence theory based on such terms as idealization, crystallization, and intrusive thinking. After proving May and Marcher as limerent lovers, each pursuing a love style fundamentally at odds with the love style of the other, this article finally, based on Sigmund Freud’s notion of cathexis, concludes it is Marcher’s narcissism or self-cathexis that bars the doors of proper communication and mutual recognition.